Environmental sustainability of milk production: a comparative environmental impact analysis and sustainability evaluation - Singh, Alok Bihari; Bhakar, Vikrant; Gaurav, Gaurav; Khandelwal, Chandni; Sarkar, Prabir; Singh, Harpreet; Dangayach, Govind Sharan (Frontiers in Sustainability, 2024)
CONTEXT: Assessing the sustainability of milk production in India (the largest milk producer country in the world) is essential to ensure that the dairy industry can meet the growing demands for dairy products while minimizing its negative impact on the environment, society, and the well-being of the people involved in the sector. OBJECTIVE: Current research is intended to compare the emissions associated with packed milk production in two contrasting states, Punjab (an Indian state with helpful agricultural resources and plenty of water) and Rajasthan (a state with a significant desert area) of India. The dairy industry has to undergo different production processes, including livestock, feed, farming, transportation, processing, packaging, and distribution. All of these production steps generate environmental impacts. This study aims to compare the environmental impacts of milk production in Punjab and Rajasthan by understanding the variation in the ecological effects due to the modifications adopted in dairy practices. METHODS: This study uses Umberto LCA+ with Ecoinvent v3.6 dataset as a Life cycle assessment (LCA) tool and data collected from milk producers and processing plants. The primary data was collected from farmers (milk producers) and dairy plants (processing plants), real-time observations, and inputs from the processing plant staff. The LCA analysis was performed, including parameters such as feed agriculture, milking, storage, transportation, processing, packaging, and distribution. RESULTS AND CONCLUSIONS: The analysis results indicate that milk production in Punjab is more environmentally efficient than in Rajasthan, and the feed required for cattle is a critical environmental impact-generating activity along with the selection of packaging material for processed milk. SIGNIFICANCE: The current article assesses the environmental implications of milk production. The study employs a comprehensive analysis to inform sustainable practices and reduce the ecological footprint of this crucial industry.